2022
DOI: 10.1161/circulationaha.121.058607
|View full text |Cite
|
Sign up to set email alerts
|

Novel Smooth Muscle Ca 2+ -Signaling Nanodomains in Blood Pressure Regulation

Abstract: Background: Ca 2+ signals in smooth muscle cells (SMCs) contribute to vascular resistance and control blood pressure. Increased vascular resistance in hypertension has been attributed to impaired SMC Ca 2+ signaling mechanisms. In this regard, transient receptor potential vanilloid 4 (TRPV4 SMC ) ion channels are a crucial Ca 2+ entry pathway in SMCs. However, their role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…Another study found that activated TRPV1 inhibited VSMC proliferation, migration, and ROS production by upregulating the expression of PPARα ( Zhou et al, 2021 ). Additionally, TRPV4 channel activity has been found to increase vasoconstriction and elevate resting blood pressure in mice and patients with hypertension ( Chen et al, 2022 ).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Another study found that activated TRPV1 inhibited VSMC proliferation, migration, and ROS production by upregulating the expression of PPARα ( Zhou et al, 2021 ). Additionally, TRPV4 channel activity has been found to increase vasoconstriction and elevate resting blood pressure in mice and patients with hypertension ( Chen et al, 2022 ).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Isolated ECs and SMCs were fixed by incubation with 4% PFA at room temperature for 15 min and then permeabilized by treatment with PBS containing 0.2% Triton‐X for 1 h. The cells were then treated with 5% normal donkey serum for 1 h. ECs were subsequently incubated with monoclonal CD31 antibody (1:100; #RM5201; Invitrogen 18 ) for 1 h at room temperature. SMCs were incubated with FITC‐conjugated anti‐α‐actin antibody (1:500; F3777; Sigma Aldrich 18 , 27 for 1 h at room temperature. After washing the cells three times with PBS, nuclei were stained by incubating with 0.3 μmol/L DAPI (Invitrogen) for 10 min at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…For SMC isolation, 27 arterial segments were transferred to a 12 × 75 mm borosilicate glass culture tube containing 1 ml dissociation solution (145 mmol/L NaCl; 4 mmol/L KCl; 1 mmol/L MgCl 2 ; 10 mmol/L HEPES; 0.05 mmol/L CaCl 2 ,10 mmol/L glucose; pH 7.3) and 0.5 mg/ml bovine serum albumin (BSA) and incubated for 10 min at room temperature (~24°C). The solution was then replaced with 1 ml dissociation solution containing 1 mg/ml papain (Sigma Aldrich) and 0.5 mg/ml dithiothreitol (Sigma Aldrich), and incubation was continued at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Isoforms of TRPC, TRPV, and TRPM have been identified in the vascular system and are emerging as important regulators of vascular tone and function, particularly TRPC1, TRPC3, TRPC6, TRPC7, TRPV1, TRPV4, and TRPM7. [9][10][11][12] They have also been linked pathological conditions associated with endothelial dysfunction, vascular contraction, and arterial remodeling, processes that characterize the vasculopathy of hypertension. 12 Further developing this notion, Chen and colleagues 10 demonstrate that vascular TRPV4 channels are critically involved in the pathophysiology of hypertension.…”
Section: Article See P 548mentioning
confidence: 99%
“…15 Although most previous studies have focused on dysregulation of TRPV4 channels in endothelial cells in hypertension, it is now evident that VSMCs are also important. Using inducible TRPV4 SMC −/− mice, Chen et al 10 show that TRPV4 SMC channels increase blood pressure in basal conditions and contribute to blood pressure elevation in angiotensin II-induced hypertension. The authors go on to unravel underlying molecular mechanisms and demonstrate subpopulations of differentially regulated TRPV4 channels with opposing actions.…”
Section: Article See P 548mentioning
confidence: 99%